Analisis Pengaruh Pemasaran Digital dan Kualitas Produk Terhadap Kepuasan Pelanggan Pada Usaha Mikro Kecil Dan Menengah (UMKM) di Kota Bengkulu - Yusmika, Dera; Gustini, Gustini; Azuwandri, Azuwandri (Jurnal Administrasi Bisnis Nusantara, 2026)
This study aims to determine the effect of competency-based training and development on the improvement of human resource quality at the Department of Industry and Trade of Bengkulu Province. The study is based on the importance of enhancing the competencies of government personnel in order to meet dynamic and competitive work demands. The research employed a quantitative method with an associative approach, and data were collected through questionnaires from 50 employees. Data analysis included quality tests, validity and reliability tests, classical assumption tests (normality and heteroscedasticity), multiple linear regression, as well as t-tests and F-tests. The results show that competency-based training (X1) has a positive and significant effect (t-value 5.283; Sig. 0.000). Likewise, competency-based development (X2) also has a positive and significant effect (t-value 6.239; Sig. 0.000). Simultaneously, both variables (X1 and X2) have a positive and significant effect (F-value 30.474; Sig. 0.000). The coefficient of determination indicates that training and development explain 56.6% of the variation in human resource quality, while the remaining 43.4% is influenced by other factors not examined in this study. This study concludes that competency-based training and development play a crucial role in improving the effectiveness and quality of human resources at the Department of Industry and Trade of Bengkulu Province. .